2013
DOI: 10.1021/nl304244h
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the Anomalous Tensile Properties of WS2 Nanotubes by in Situ Transmission Electron Microscopy

Abstract: Mechanical properties and fracture behaviors of multiwalled WS2 nanotubes produced by large scale fluidized bed method were investigated under uniaxial tension using in situ transmission electron microscopy probing; these were directly correlated to the nanotube atomic structures. The tubes with the average outer diameter ∼40 nm sustained tensile force of ∼2949 nN and revealed fracture strength of ∼11.8 GPa. Surprisingly, these rather thick WS2 nanotubes could bear much higher loadings than the thin WS2 nanotu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
37
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 30 publications
1
37
0
Order By: Relevance
“…They can act as nucleation sites for the onset of deformation, when subjected to stress [2][3][4] . When exposed to chemical functional groups, defects can also behave as highly reactive sites and efficiently trap different molecules 5,6 .…”
mentioning
confidence: 99%
“…They can act as nucleation sites for the onset of deformation, when subjected to stress [2][3][4] . When exposed to chemical functional groups, defects can also behave as highly reactive sites and efficiently trap different molecules 5,6 .…”
mentioning
confidence: 99%
“…In this work, we design an in situ transmission electron microscopy (TEM) probing technique [17][18][19][20] to investigate the initial stages of the 2D crystal cleavage, which is defined here as the 'nanomechanical cleavage', using MoS 2 atomic layers as a model material. By precisely manipulating an ultra-sharp metal probe to contact the pre-existing crystalline steps of the MoS 2 single crystals, atomically thin flakes are delicately peeled off, selectively ranging from a single, double to more than 20 atomic layers.…”
mentioning
confidence: 99%
“…The applications of nontraditional abrasives in CMP technology require direct insight into the particles' mechanical properties, such as elastic modulus (E), Poisson ratio (ν), hardness (H), interfacial adhesion and friction, as well as their size-dependent effects [4]. In order to acquire quantitatively this information, different measurement methods have been developed, mainly including nano-indentation with an atomic force microscope (AFM) [19,20], in-situ compression, bend and tension [21,22] by a transmission electron microscope-scanning probe microscope (TEM-SPM) platform. So far, in-situ high resolution TEM is considered as the most advanced instrument to accurately measure the mechanical properties of micro/nano-scaled samples.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
“…The dislocation nucleation from a free surface and plastic deformation between the SPM probe and the sample contact surface were observed in-situ. Moreover, Tang et al [22] analyzed the tensile properties of multiwalled WS 2 nanotubes under uniaxial tension using in-situ TEM tests. It was found that the thick WS 2 nano-tubes could sustain a much higher tensile force than "defect-free" thin nano-tubes.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%